Look me in the eye my life with Asperger's - Robison, John Elder (Crown Publishers, 2007)
Look Me in the Eye is a moving and unexpectedly funny memoir of growing up with Asperger's syndrome (a form of high-functioning autism) at a time when the diagnosis didn't even exist. Along the way it also tells the story of two brothers born eight years apart yet devoted to each other: the author and his younger brother, who would grow up to become Augusten Burroughs, author of the bestselling Running with Scissors and who has contributed a beautiful foreword to this book. For anyone who loved The Curious Incident of the Dog in the Night-time, and of course Running with Scissors.--Source other than Library of Congress.